Contribution of Bamboos in Livelihood of North - Eastern Region of India - Bahar, Nawa (Indian Forester, 2014)
Bamboos are extremely useful plant species. It is considered as a poor man’s timber. It is the most suitable soil binder to prevent erosion in fragile ecosystem, canal banks and steep terrain. Bamboos are used extensively in constructions and handicrafts for making a wide array of articles of day to day use, in rural area for irrigation and fuel, as food (bamboo shoot), in industry (mainly for pulp). In rural area, homesteads may have a few clumps of one of the many species of bamboo for household use such as construction of home, shed and fences. One of the most important contributions of bamboo to modern - day man is in the production of paper. It is considered as cash crop having low gestation period, fast growth, diversified uses and easier marketability. Although, meagre attempts have been done to grow bamboo outside the forest, however, concerted efforts are still required to cover large area. This will go a long way in providing necessary income to marginal farmer and to generate employment and reduce poverty in north - eastern region.